Cyanobacterial Biomass Pigments as Natural Sensitizer for TiO2 Thin Films - Karen Patiño-Camelo; Carlos Diaz-Uribe; Euler Gallego-Cartagena; William Vallejo; Vincent Martinez; Cesar Quiñones; Mikel Hurtado; E. Schott (International Journal of Photoenergy)
In this work, we studied the effect of TiO2 sensitization with dry biomass extracted of cyanobacteria on the degradation of methylene blue dye (AM). Cyanobacterial cultures isolated from water samples were collected from the swamp of Malambo in Colombia; two main genera of cyanobacteria were identified, and they were cultivated with BG-11 culture medium. The concentrations of chlorophyll a in the exponential and stationary phases of growth were measured; the phycobilin content was quantified by spectrophotometry. Thin films of TiO2 were deposited by a doctor blade method, and they were sensitized by wet impregnation. Furthermore, a methylene blue (MB) photodegradation process was studied under visible light irradiation on the cyanobacterial biomass sensitized TiO2 material (TiO2/sensitizer); besides, the pseudo-first-order model was used to obtain kinetic information about photocatalytic degradation. The results showed that the BG-11+ treatment reported a higher amount of dry biomass and phycobiliproteins. After the sensitization process, the TiO2/sensitizer thin films showed a significant red shift in the optical activity; besides the thin film roughness decreasing, the TiO2/sensitizer showed photocatalytic activity of 23.2% under visible irradiation, and besides, the kinetic (kap) constant for TiO2/sensitizer thin films was 3.1 times greater than the kap value of TiO2 thin films. Finally, results indicated that cyanobacterial biomass is a suitable source of natural sensitizers to be used in semiconductor sensitization.